Emergence and Survival of New Businesses Econometric Analyses - Falck, Oliver (Contributions to Management Science, 2007)
Two very topical research questions are addressed in this book: Which are the determinants of new business formation and their survival, and will business start-ups, especially in the service sector, create employment and thereby generate growth? The analysis is based on a unique dataset consisting of the population of all businesses with at least one employee under social security in Germany in all private industries (manufacturing and services). State-of-the-art econometric techniques are used throughout the book, taking into account the multi-dimensional character of the determinants. Using Germany as an example, the book gives a comprehensive review on entrepreneurial activity, and draws the general conclusion that new businesses should not be subsidized with a watering can.